Effect of vitamin A on recovery from the acute phase of multiple sclerosis-related optic neuritis, double-blind, randomized, placebo-controlled trial - Shiva Rahimi-Dehgolan; Maryam Masoudi; Shahram Rahimi-Dehgolan; Amir Reza Azimi; Mohammad Ali Sahraian; Seyed Mohammad Baghbanian; Abdorreza Naser Moghadasi (Caspian Journal of Internal Medicine, 2023)
Background: Optic neuritis (ON) is one of the main neuro-ophthalmic presentations of multiple sclerosis (MS), and it causes optic nerve atrophy and axonal loss. However, so far, there is no effective treatment to improve long-term outcomes. Methods: In a double-blind placebo-controlled randomized clinical trial, 50 patients with MS-related ON were allocated into two arms (24 in the control group and 26 in the intervention group) receiving either 25000IU retinyl palmitate or an identical placebo for six months. Visual evoked potential (VEP), visual acuity, and the retinal nerve fiber layer (RNFL) thickness were evaluated and compared before and after the treatment. Results: RNFL thickness reduction in the affected eyes at sixth month compared to the baseline were 14.81 and 19.46 μm, in the intervention and control groups, respectively (P=0.017). However, VitA therapy did not affect visual acuity and VEP. Conclusion: Vitamin A supplementation in the patients with acute ON in MS could lessen optic nerve axonal loss.